Linguo-didactic approach to terms of phraseological character in the sphere of economics; Коммуникативные аспекты языка и культуры; Ч. 1 - Fedulenkova T. N. (Актуальные проблемы лексикологии, фразеологии, 2015)
Заглавие с титульного экрана